Self‐Assembled Nanostructures of Quantum Dot/Conjugated Polymer Hybrids for Photonic Synaptic Transistors with Ultralow Energy Consumption and Zero‐Gate Bias - Ercan, Ender; Lin, Yan‐Cheng; Yang, Wei‐Chen; Chen, Wen‐Chang (Advanced functional materials, 2022)
Herein, it is reported the influence of solution processing and treatments, such as adding marginal solvent, ultrasonication, and UV treatment, on the resulting perovskite (CsPbBr3) quantum dot (QD)/poly(3‐hexylthiophene) (P3HT) composite nanofibril films (CNFs) to improve the charge dissociation and photonic synaptic performance. A photonic synaptic transistor with CNFs can perform fundamental functions, including short‐term plasticity, long‐term plasticity, spike‐number‐dependent, and spike‐time‐dependent plasticity, to mimic sensing, computing, and memory functions. Notably, a synaptic device with CNFs presents an ultralow energy consumption of 0.18 fJ and zero‐gate operation. The superior performance of synaptic devices with CNFs can be attributed to two factors: (i) homogeneous axial distribution of the QDs and (ii) the formation of P3HT nanofibrils and co‐aggregates. Therefore, enhanced interfacial charge transfer between QDs and P3HT, ensuring decent carrier transport capability, is achieved. Collectively, the composite artificial synapse successfully provides an effective guide that offers a new perspective for the fabrication of one‐dimensional self‐assembled nanostructure‐based artificial synapses emulating human‐like memory, neuromorphic computing, and artificial intelligent systems. Semiconducting self‐assembled composite nanostructures via solution processing is a promising strategy to improve the charge dissociation and photonic synaptic performance. In this study, quantum dot/poly(3‐hexylthiophene) nanofibrils are studied to understand the morphology/optoelectronic relation. The composite artificial synapse exhibits fundamental functions, including short‐term plasticity, long‐term plasticity, and spike‐number‐dependent and spike‐time‐dependent plasticity with ultralow energy consumption of 0.18 fJ and zero‐gate operation.